Implementasi Reward Dalam Meningkatkan Questioning Skill Pada Mata Pelajaran Sejarah Kebudayaan Islam (SKI) Siswa Kelas VIII MTs Nurul Huda - Fatimah Ahmad; Khairuddin Khairuddin; Gita Ramadani (Jurnal Dirosah Islamiyah, 2021)
The background of this research is that in the teaching and learning process MTs Nurul Huda has applied rewards. The application of rewards is a means to encourage students to improve students' questioning skills in the learning process. The objectives of this research are: to find out whether the implementation of rewards can improve Questioning Skills in the subject of Islamic Cultural History for class VIII MTs Nurul Huda. This study uses a qualitative approach. The subjects of this study were principals, teachers and students. Collecting data in this research using observation, interviews and documentation. The results of this study are to give rewards to students, generate or foster enthusiasm for students' curiosity about learning so that students ask a lot of questions. Thus, students' asking skills automatically increase